2006
DOI: 10.3892/or.15.2.311
|View full text |Cite
|
Sign up to set email alerts
|

Matrilysin (MMP-7) degrades VE-cadherin and accelerates accumulation of beta-catenin in the nucleus of human umbilical vein endothelial cells

Abstract: Abstract. Matrilysin, MMP-7, is an important target for antimetastasis therapy of colorectal cancer because it is a strong proteolytic factor secreted from the cancer cell itself and it induces tumor angiogenesis. In a previous report, we showed that matrilysin accelerated human umbilical vein endothelial cell (HUVEC) proliferation in low serum conditioned medium. In the present study, we show that matrilysin stimulation decreased VE-cadherin expression, induced accumulation of beta-catenin in the nucleus of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 16 publications
(18 reference statements)
0
37
2
1
Order By: Relevance
“…Thus, EBV and KSHV may promote B-cell proliferation by stabilizing ␤-catenin (34). ␤-catenin release from cadherins has been implicated in Wnt-dependent and Wnt-independent induction of transcription during cancer (34,39,44). While we did not observe increased ␤-catenin levels in cells coexpressing K5 and LANA and while K5 reduced the expression of Wnt target proteins (Fig.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Thus, EBV and KSHV may promote B-cell proliferation by stabilizing ␤-catenin (34). ␤-catenin release from cadherins has been implicated in Wnt-dependent and Wnt-independent induction of transcription during cancer (34,39,44). While we did not observe increased ␤-catenin levels in cells coexpressing K5 and LANA and while K5 reduced the expression of Wnt target proteins (Fig.…”
Section: Discussioncontrasting
confidence: 51%
“…It was previously reported that ␤-catenin released from the cadherin scaffold induces the transcription of Wnt-regulated genes independently of Wnt signaling (39,50). Therefore, we examined the expression of the Wnt-/␤-catenin-regulated proteins cyclin D1 and survivin.…”
Section: Methodsmentioning
confidence: 99%
“…As a possible underlying mechanism, this effect could be mediated by degradation of VE-cadherin and nuclear accumulation of b-catenin in HUVECs (Ichikawa et al, 2006). Additionally, in light of the secretion of VEGF (Huo et al, 2002) and CTGF (Brigstock, 1999) by HUVECs, the HUVEC proliferation induced by MMP-7 could also be explained by liberation of CTGF-sequestered VEGF, helping endothelial cells use the self-made VEGF.…”
Section: Mmp-7 Activates Latent Vegf From Fibroblasts T-k Ito Et Almentioning
confidence: 99%
“…It has been demonstrated previously that when matrix metalloproteinases (MMPs) cleave an extracellular classic cadherin domain, β-catenin is removed from its position near the cell membrane and in many cases will translocate to the cell nucleus (Lochter et al, 1997;Sanceau et al, 2003;Ichikawa et al, 2006;Cowden Dahl et al, 2008;Dwivedi et al, 2009;Zheng et al, 2009;Lynch et al, 2010). This translocation is associated with cell movement (reviewed in Tanaka et al, 2011).…”
Section: Matrix Metalloproteinases and Cell Movementmentioning
confidence: 99%